Increasing Children's Capacity At Al-Azhar Syifa Budi Kindergarten To Maintain Healthy Teeth - Yuanita Anwaristi, Aprilia (Journal of Community Capacity Empowerment, 2024)
Children's teeth are a determinant of the growth and development of the oral cavity because the child's milk teeth will determine the child's permanent teeth. Therefore It is important to monitor and monitor the growth of teeth in children here. The aim of promoting health on the correct way to brush your teeth to students is to increase students' knowledge about the steps for brushing teeth, how to brush teeth correctly, and demonstrate the correct way to brush your teeth with the help of a dental phantom, so students can get used to it. to clean and brush teeth. Lifetime live in everyday life. This exercise uses the lecture and demonstration method brush teeth, question and answer and discussion. Before counseling is carried out, a post test is given to students as material evaluate activities to find out students' knowledge about brushing teeth correctly before extension activities and after extension activities. After the lecture and demonstration/demonstration. A question and answer session was held after the counseling material was completed delivered to participants and delivered. From the results of the tooth brushing education, it can be concluded as follows: Al-Azhar Kindergarten student Syifa Budi can understand the stages of brushing teeth. Al-Azhar Syifa Budi Kindergarten students can practice/demonstrate the method brush your teeth properly and correctly. Al-Azhar Kindergarten student Syifa Budi understands how to maintain healthy teeth